2021
DOI: 10.1016/j.colegn.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in cancer survivorship care: A cross-sectional study of telehealth use among cancer nurses in Australia

Abstract: Background: Cancer survivors living in rural and remote areas of Australia experience poorer health outcomes than their metropolitan counterparts. Telehealth provides opportunities for the delivery of survivorship care.Aim: To investigate the preparedness of the cancer nursing workforce in Australia to deliver survivorship care using telehealth.Methods: Through a nationally disseminated online survey, nurses' perceptions, attitudes and use of telehealth to deliver cancer survivorship care were assessed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As it was mentioned earlier, the functional characteristics of the technology to be free of effort and compatible with the desired need are good determinants for adopting telemedicine by users. Furthermore, it has been found that some studies use a single theoretical model [33], [40], [43], while others use more than one model [13], [28], [32], [34]- [37], [42], [44], [45]. Although the TAM and UTAUT are the based models in most literature as it was mentioned above, other factors from different models were integrated with them to represent the acceptance in different contexts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As it was mentioned earlier, the functional characteristics of the technology to be free of effort and compatible with the desired need are good determinants for adopting telemedicine by users. Furthermore, it has been found that some studies use a single theoretical model [33], [40], [43], while others use more than one model [13], [28], [32], [34]- [37], [42], [44], [45]. Although the TAM and UTAUT are the based models in most literature as it was mentioned above, other factors from different models were integrated with them to represent the acceptance in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…[28]- [31], and the other 5 studies on telemonitoring [32]- [36]. A total of 3 studies were dedicated to remote mental health services -Telepsychotherapy [37]- [39], while 4 studies centered around telerehabilitation [40], [41], and tele palliative care [42], [43], each with 2 studies.…”
Section: B Telemedicine Applicationsmentioning
confidence: 99%
See 3 more Smart Citations